2020
DOI: 10.1101/2020.04.23.058123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FOXO1 promotes HIV Latency by suppressing ER stress in T cells

Abstract: Quiescence is a hallmark of CD4 + T cells latently infected with HIV-1. While reversing this quiescence is an effective approach to reactivate latent HIV from T cells in culture, it can cause deleterious cytokine dysregulation in patients. Here we report that FOXO1, a key regulator of T-cell quiescence, promotes latency and suppresses productive HIV infection. In resting T cells, FOXO1 inhibition induces ER stress and activates two associated transcription factors: activating transcription factor 4 (ATF4) and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…This TF is associated with a quiescent central memory T cell (Tcm) phenotype, consistent with the hypothesis that cells that adopt a quiescent Tcm phenotype are more prone to latent infection (Garaud et al, 2017). Interestingly, a related Forkhead TF, FOXO1, has also recently been reported to promote HIV latency (Roux et al, 2019;Vallejo-Gracia et al, 2020). In addition to these known HIV-regulating TFs, several TFs with no known role in HIV transcription were identified by our study, and defining their role in latency will likely lead to the discovery of new mechanisms of transcriptional repression for HIV.…”
Section: Discussionsupporting
confidence: 75%
“…This TF is associated with a quiescent central memory T cell (Tcm) phenotype, consistent with the hypothesis that cells that adopt a quiescent Tcm phenotype are more prone to latent infection (Garaud et al, 2017). Interestingly, a related Forkhead TF, FOXO1, has also recently been reported to promote HIV latency (Roux et al, 2019;Vallejo-Gracia et al, 2020). In addition to these known HIV-regulating TFs, several TFs with no known role in HIV transcription were identified by our study, and defining their role in latency will likely lead to the discovery of new mechanisms of transcriptional repression for HIV.…”
Section: Discussionsupporting
confidence: 75%
“…The DE isoform data confirms the involvement of NFKB-complex via significant 4-fold increases in relevant NFKBIA and BIRC2 isoform TPMs upon TNF-alpha treatment. Of particular note, is the highly significant (p-adj<0.1) paradoxical downregulation of a PSAT1 isoform given that previous studies have found this gene to be enriched during Tat-elicited cell proliferation in productive HIV infection (43) and during FOXO1-inhibition elicited latency reversal in HIV-infected CD4 T-cells (44). This paradoxical result can be reconciled by close inspection of its exon connectivity (Figure 4B) , which reveals that the downregulated isoform (NM_021154.4) lacks Exon 8 and results in a variant with 6-to 7-fold lower activity compared to the standard NM_058179.4 isoform that retains this exon (45).…”
Section: Resultsmentioning
confidence: 99%
“…The reversal of double-positive cells after sorting may reflect the intrinsically stochastic transcription of HIV-1 (86)(87)(88). Latent cell lines are notoriously sensitive to cellular stresses, which cause reactivation (89)(90)(91). It is, therefore, possible that the less stable GFPpositive cells represent cells that are temporarily activated, and which slowly revert back to a latent state.…”
Section: Discussionmentioning
confidence: 99%